DINAMIKA KEBERLANGSUNGAN TABUIK PARIAMAN - Asril Asril (Ekspresi Seni : Jurnal Ilmu Pengetahuan dan Karya Seni, 2011)
The existence of Tabuik has undergone some dynamics of change in a variety of situations. The tug of war in a number of situations and political interest between government and community is just like a wave of life. It is too often the case that the dynamics reach the point where there should be a willingness to shift and the loss of some symbols of tabuik‟s ritual and magical power as a cultural obligation for Pariaman community. The role of the government as a player in the dynamics of tabuik‟s existence can be regarded as “positive patronage” for the sustainability of tabuik in future.